Chars from gasification of coal and pine activated with K2CO3: Acetaminophen and caffeine adsorption from aqueous solutions - Galhetas, M. (2014)
The high carbon contents and low toxicity levels of chars from coal and pine gasification provide an incentive to consider their use as precursors of porous carbons obtained by chemical activation with K2CO3. Given the chars characteristics, previous demineralization and thermal treatments were made, but no improvement on the solids properties was observed. The highest porosity development was obtained with the biomass derived char (Pi). This char sample produced porous materials with preparation yields near 50% along with high porosity development (ABET 1500 m2 g1). For calcinations at 800 C, the control of the experimental conditions allowed the preparation of samples with a micropore system formed almost exclusively by larger micropores. A mesopore network was developed only for samples calcined at 900 C. Kinetic and equilibrium acetaminophen and caffeine adsorption data, showed that the processes obey to a pseudo-second order kinetic equation and to the Langmuir model, respectively. The results of sample Pi/1:3/800/2 outperformed those of the commercial carbons. Acetaminophen adsorption process was ruled by the micropore size distribution of the carbons. The caffeine monolayer capacities suggest a very efficient packing of this molecule in samples presenting monomodal micropore size distribution. The surface chemistry seems to be the determinant factor that controls the affinity of caffeine towards the carbons.